2017
DOI: 10.9774/tandf.4700.2017.se.00004
|View full text |Cite
|
Sign up to set email alerts
|

Small Business Social Responsibility: More than Size

Abstract: B e n d ell, Je m (2 0 1 7) C u r r e n cy in n ov a tio n fo r s u s t ai n a bl e fin a n ci n g of S M E s: c o n t ex t, c a s e s t u dy a n d s c al a bility. Jou r n al of Co r p o r a t e Citiz e n s hi p, 2 0 1 7 (6 7). p p. 3 9-6 2. Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 3 0 7 0/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Accordingly, we identified major value dimensions of SME top managers (benevolence, achievement, power, and conformity values) that mostly drive CS. Our literature review contributes to calls for research by academics, regulators, and practitioners, to further investigate the development of CS in SMEs (Berk 2017). Moreover, our findings contribute to social interest as well as the management literature by deriving recommendations and practical implications.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Accordingly, we identified major value dimensions of SME top managers (benevolence, achievement, power, and conformity values) that mostly drive CS. Our literature review contributes to calls for research by academics, regulators, and practitioners, to further investigate the development of CS in SMEs (Berk 2017). Moreover, our findings contribute to social interest as well as the management literature by deriving recommendations and practical implications.…”
Section: Introductionmentioning
confidence: 64%
“…Additionally, the well-treatment of employees is a key characteristic of SMEs (Hammann et al 2009) due to the more direct and intense relation between SME executives and their employees (Torrès 2003). However, although existing literature indicated that SMEs engage in CS, several studies showed that most SMEs do not comprehend or use the term "CS" even when interacting in CS (Berk 2017;Giovanna and Lucio 2012) and oftentimes perceive the term CS as unattractive and off-putting (Grayson and Dodd 2007). Arguing that most SME executives do not view CS as an external but rather as "an integral part of the way they manage their firm" (Jenkins 2009;Kechiche and Soparnot 2012, p. 98).…”
Section: Domain Theories: Greenblushing and Corporate Sustainability In Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are R. Peckham, J. Lepoutre, A. Heene and others. The research highlights issues such as the nature of world economic crisis in the context of civilizational development of world and the development of anti-crisis measures, although fragmented [1][2][3][4][5][6][7], As for business social responsibility researchers, the greatest attention to these issues was paid by A. Berk, M. Morsing, L. J. Spence and others [8][9][10][11][12].…”
Section: Analysis Of Recent Researchmentioning
confidence: 99%
“…Accounting information systems (AIS) guide the best action in allocating scarce resources in business and economic activity. AIS can help businesses, especially SMEs, overcome short-term problems in financing, expenditures, and cash flows by applying the monitoring and control mechanism (Deaconu and Buiga 2015;Kunttu and Torkkeli 2018;Berk 2017). Applying the accounting information can help SMEs in a very dynamic and competitive environment integrate the operational elements into long-term strategic planning (Gimede 2004;Burch 2018;Whah and Shiang 2018;Kunttu and Torkkeli 2018).…”
Section: Introductionsmentioning
confidence: 99%